Utilization of Plant Growth-Promoting Bacteria for Plant Diseases Bio-control - Padhi, S K; Khamari, Bhagyashree (International Journal of Psychosocial Rehabilitation, 2025)
In sustainable agriculture, the management of plant disease has become a dispute for plant pathologists. Plant growth promoting rhizobacteria (PGPR) is a major group of microbes that plays a key role in plant pathogens biocontrol. PGPR can greatly enhance germination of seed, root development and water absorption. The most widely studied class of PGPB is the colonization of root surfaces by plant growth-promoting rhizobacteria (PGPR). Recent progress has been made in our understanding of their colonizing capacity, diversity, formulation, and action mechanism, and applications that promote their development as dependable agents of bio-control against plant pathogens. Pathogenic microorganisms that affect plant health are a significant and persistent threat to food production and the stability of the world's ecosystems. The rising cost of pesticides, especially in the less prosperous regions around the world, and demand of consumer for pesticide-free food has led to a quest for alternatives for these products. There are also a variety of particular diseases for which chemical solutions are less, non-existent or ineffective. Therefore, biological control is regarded as an alternative or additional way to minimize the use of chemicals in agriculture. This study reviews the principles and action mechanisms of plant growth-promoting bacteria and their use or potential use for plant disease biological control